Effects of oral lubrication on satiety, satiation and salivary biomarkers in model foods: A pilot study. (1st October 2021) - Stribițcaia, Ecaterina; Gibbons, Catherine; Sier, Joanna; Boesch, Christine; Blundell, John; Finlayson, Graham; Sarkar, Anwesha
Abstract: With a dramatic increase in overweight and population with obesity over the last decades, there is an imminent need to tackle this issue using novel strategies. Addressing obesity issues by generating satiety in food to reduce energy intake has been one of those prominent strategies and often textural interventions have been used to generate satiety, specifically in short-term trials. This study aimed to investigate the role of preloads varying in their oral lubricating properties on appetite sensations, food intake, salivary friction and concentration of salivary biomarkers (proteins, α -amylase and mucins) in collected human saliva (n = 17 healthy participants). The preloads were model foods (flavoured hydrogels) either high or low in their lubricating properties, assessed both by instrumental and sensorial measurements. The results showed that hunger and desire to eat decreased immediately after preload and remained decreased for 10 and 20 min, respectively, after preload in the high lubricating condition compared to control (all p < 0.05 ). Fullness increased immediately after preload and remained increased for 10 and 20 min, respectively, after preload in high lubricating condition compared to control ( p < 0.05 ). However, after controlling the values for baseline, such significant effect of the intervention did not exist anymore. Only the effect of time is observed. Consuming high lubricating hydrogels showed no effect on food intake and salivary biomarkers in this pilot study. Salivary lubrication correlated with feeling of fullness. Considering the issue of large time-interval (30 min) between preload and next meal in this study, it is worthwhile investigating the immediate effects of oral lubrication on appetite control, food intake and salivary biomarkers.